The paradoxes of "school management" and the movement of despolitization in the brazilian school: a reading to the national newspapers of the education area in the years of 1990 to 2000 - Adreana Dulcina Platt; Bruna Silva Duarte; Sílvio Ancízar Sanches Gamboa; Frederico Augusto Garcia Fernandes (Universidade Federal de Santa Catarina, 2019)
This study deals with the bibliographic review of articles that have socialized educational productions in Education, whose conceptual core was "educational management" / "school management" / "democratic management in school" and, as a method, historical-critical materialist and dialectical. We start from the Marxian categories for thinking the paradox manifested  in models that support the discourse of the scientific administration for the construction of a political-pedagogical routine based on the revolutionary logic. We highlight the categories of "Totality" and "More-Value" to confront the studies. In order to verify the phenomenon in the scientific production in Education, we rely on the research of the type "Study of the Art", as an interesting methodological device of academic update (bibliographical revision), since it announces the tendencies that sustain the evolution of the thought scientific community about a particular object and / or social phenomenon. The articles for analysis are from national academic journals available in the Scielo database, from 1990 to 2000. For selecting the articles we focused on the following metadada: "School Management" / "Educational Management" and / or "Democratic Management in School ". This search resulted in 22 articles collected and 5 articles analyzed once they fulfilled all the variables indicated. Finally, we consider the existence of the paradox constituted by the authors who based their studies on the historical-critical and dialectical materialist method, attentive to the nature of the specific categories of economy and social formation to unveil reality, but incorporating the categories of Scientific Administration, mainly in the "managerialist" argumentation, naturalizing them in the rationalization of a school routine of pretension against hegemonic.